Corporate social responsibility: a comprehensive framework –Bangladesh perspective - Haque, Samina (© 2012 European Journal of Social Sciences, 2016)
This article was published in European Journal of Social Sciences [© 2012 European Journal of Social Sciences] The article website is at: http://www.europeanjournalofsocialsciences.com/issues/EJSS_36_2.html